Prevalence of undernutrition and associated factors in young children in Malaysia: A nationwide survey - Lee, Way Seah; Jalaludin, Muhammad Yazid; Khoh, Kim Mun; Kok, Juan Loong; Nadarajaw, Thiyagar; Soosai, Anna Padmavathy; Mukhtar, Firdaus; Fadzil, Yong Junina; Anuar Zaini, Azriyanti; Mohd-Taib, Siti Hawa; Rosly, Rozanna M.; Khoo, An Jo; et al. (Frontiers in Pediatrics, 2022)
Introduction: Undernutrition in young children is a significant public health problem globally. We determined the prevalence of and factors predisposing to stunting and underweight in children aged 1 to 5 years in Malaysia. Materials and Methods: Data were extracted from a cross-sectional nationwide campaign involving healthy children aged 1-5 years conducted over a 4-month period in 2019. We obtained information on demography, parental height and risk factors of undernutrition and anthropometric measurements (height and weight) of children enrolled. Age and sex-specific z-score for length/height-for-age (HAZ), weight-for-age (WAZ), body mass index (BMI) z-score (BAZ) and weight-for-height/length (WFH) z-score (WFHZ) were obtained using World Health Organization growth standards. The following definitions were used: (a) HAZ < -2 SD as stunted and -2 to -1 SD as at risk of stunting; (b) WFHZ < -3 SD as severe, -3 to < -2 SD as moderate wasting, and -2 to < +1 SD as normal; (c) WAZ -2 to -1 as at risk of underweight; (d) BAZ +1 to < +2 SD as at risk of and > +2 SD as overweight. Results: Of the 15331 children surveyed, prevalence of stunting and at risk of stunting were 16.1% and 20.0%, severe and moderate wasting were 4.0% and 6.1%, while 21.1% was at risk of underweight. Prevalence of at risk of and overweight 14.2% and 7.3%, respectively. One in fifth (25.0%) children had at least one form of undernutrition (stunting and/or underweight/wasting). Of the 1412 (13.2%) children reported to have risk factors of undernutrition, 47.2% had feeding difficulties, 44.8% had poor dietary intake and 8.0% had both. Boys, paternal height < 156 cm and poor dietary intake were significantly associated with stunting and/or wasting. Compared with children with no risk factors, children with feeding difficulties were more likely to be wasted (AOR: 1.48, 95% CI: 1.18 – 1.85), and had at least one form of undernutrition (AOR: 1.45, 95% CI: 1.25 – 1.69). Conclusions: In Malaysian children aged 1 to 5 years, dual burden of under- and overnutrition are common. Poor dietary intake and feeding difficulties were risk factors for undernutrition.